The Role of Russian Literature in the Modern Educational Space - Sevara, Otaxonova (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
The article is devoted to the role of Russian literature in the modern educational space. The author analyzes the importance of studying classical Russian literature for the formation of personality, development of speech and thinking, as well as for immersion in the history and culture of Russia. The article emphasizes the importance of Russian literature for fostering tolerance and respect for other cultures, as well as for the development of critical thinking and analytical skills. The author also notes the importance of including modern Russian literature relevant to the younger generation in the educational process. The conclusion emphasizes that preserving and developing interest in Russian literature among the younger generation is a key factor for ensuring its significant role in education and for the formation of a harmonious personality.